Creating a Danish legal language: legal terminology in the medieval Law of Scania. Issue 233 (1st July 2013) - Tamm, Ditlev; Vogt, Helle
Abstract In the decades after 1200 the kingdom of Denmark developed a corpus of provincial laws written in Danish for the three major legal provinces. With the legislation for the eastern province of Scania as a starting point, this article shows how the writing down of the law led not only to the creation of a legal language but to a written vernacular language in general. It was not until the fifteenth century that written Danish was found outside of texts; charters and narrative until that point had been written in Latin.